UNVEILING THE BENEFITS OF ENGLISH-SPEAKING CLUB: INSIGHTS FROM STUDENTS AT ONE HIGHER SCHOOL IN PALEMBANG - Muhamad Holandyah; Lenny Marzulina; Dian Erlina; Novita Angreini (Esteem Journal of English Education Study Programme, 2024)
This qualitative case study aimed to explore students' insights of practicing English speaking through participation in an English-speaking club. The three student participants in this research were selected using a purposive sampling technique. Research data were collected through semi-structured interviews using open-ended questions. Thematic analysis was then employed to analyze the data. The findings indicated that participating in the English-speaking club helps students get a supportive environment for practicing their English-speaking skills through conversation, presentation, speech, storytelling, debate, and other various speaking activities. They experience fellowship and friendship among club members, receive moral and emotional support for their views and opinions, gain more confidence and encouragement to speak English, have more opportunities to express their ideas and thoughts in English, develop their English vocabulary and expressions, receive feedback and corrections from fellow members, and have fun with their English speaking practices.